P-013 Long-term outcome of balloon angioplasty without stenting for symptomatic middle cerebral artery stenosis. (23rd July 2017) - Ueda, T; Takada, T; Takaishi, S; Fukano, T; Tatsuno, K; Yoshie, T
Abstract : Background and purpose: A recent randomized controlled trial demonstrated that aggressive medical management was superior to angioplasty with stenting for intracranial stenosis. The purpose of this study is to assess initial and long-term outcomes of balloon angioplasty without stenting for symptomatic middle cerebral artery (MCA) stenosis. Methods: We retrospectively analyzed the clinical data of 72 patients (mean age; 58.9 years old) with 84 balloon angioplasties without stenting for high-grade (and >70%) atherosclerotic stenosis of the main trunk of the MCA. All patients had experienced recurrent transient ischemic attack (TIA) or minor stroke resistant to medical treatment. We assessed perioperative and long-term outcomes such as restenosis and the recurrence of strokes. The follow-up period was a median of 63 months (range 6–171 months). Results: Balloon angioplasty was successfully 97% of procedures. During the 30 day perioperative period, a total of 3 patients suffered a stroke (4.2%) without death. A total of 23 (31.9%) patients had restenosis at a time-point that varied from 6–111 months. Diabetes mellitus was noted significantly more often in the restenosis group (39%) than in non-restenosis group (13%). Multivariate logistic regression analysis revealed diabetes mellitus (OR, 4.84; 95% CI, 1.196–19.62, p=0.027) as an independent predictor of restenosis. Restenosis and diabetes mellitus were indicated as independent predictors of recurrence of ischemic stroke and TIA. Conclusions: Balloon angioplasty without stenting for symptomatic MCA stenosis can be performed with a high successful rate and a low risk of complications. Long-term outcome data suggest that this procedure reduces the risk of further strokes. Disclosures: T. Ueda: None. T. Takada: None. S. Takaishi: None. T. Fukano: None. K. Tatsuno: None. T. Yoshie: None.